(untitled) (Raparin Journal of Humanities (RJH), 2023)
The study aimed to shed light on the extent of the auditors’ ability to audit big data, and also aimed to verify its impact on the quality of financial information. The study sample consisted of all auditors in auditing companies and offices operating in the Kurdistan Region, which numbered (93) individuals, and the valid questionnaires for statistical analysis were (87) questionnaires, equivalent to (93.5%), where the SPSS statistical program was used to analyze these data. The multiple regression analysis test was used to test the study hypotheses. The study reached a number of results, the most important of which is that there is a statistically significant correlation between the auditors’ use of a set of mechanisms and procedures and their role in auditing big data, and there is a role for auditors in the process of auditing big data in achieving the quality of financial information, meaning that procedures Mechanisms are one of the most important elements of activating the audit process in light of the big data as the conditions that must be met by the auditor such as the skills and capabilities and the contents of the reports submitted by him, and that the use of big data leads to improving the quality of financial information, because big data helps in increasing the content Knowledge of financial information by providing detailed data in a timely manner. The study made several recommendations, the most important of which was the need to raise the levels of awareness and awareness of auditors of the importance of auditing big data because of its impact on improving audit outcomes and quality, as well as improving their capabilities in the long-term.